Social Protection and Disaster Risk Management in the Philippines The Case of Typhoon Yolanda (Haiyan) - Bowen, Thomas (The World Bank, 2015)
This paper evaluates how the Philippines utilize social protection systems and programs to help households better manage disaster risk. Exposure and vulnerability to natural disasters and the effects of climate change are particularly high in the Philippines. At the same time, the Philippines has developed one of the most advanced social protection systems in the East Asia Pacific region. The Department of Social Welfare and Development is prominently integrated into the national disaster risk management framework of the Philippines, taking the lead coordinating role in disaster response activities. Consequently, social protection programs are on the frontlines of disaster response in the Philippines. This paper focuses specifically on the devastating impact of Typhoon Yolanda, which struck the country in November 2013, as a case study against which the Philippines' social protection response can be assessed